YES Problem: a(b(x1)) -> b(a(a(a(x1)))) b(a(x1)) -> a(a(x1)) a(a(x1)) -> a(c(b(x1))) Proof: String Reversal Processor: b(a(x1)) -> a(a(a(b(x1)))) a(b(x1)) -> a(a(x1)) a(a(x1)) -> b(c(a(x1))) Matrix Interpretation Processor: dim=2 interpretation: [1 0] [c](x0) = [0 0]x0, [0] [a](x0) = x0 + [1], [1 2] [0] [b](x0) = [0 3]x0 + [1] orientation: [1 2] [2] [1 2] [0] b(a(x1)) = [0 3]x1 + [4] >= [0 3]x1 + [4] = a(a(a(b(x1)))) [1 2] [0] [0] a(b(x1)) = [0 3]x1 + [2] >= x1 + [2] = a(a(x1)) [0] [1 0] [0] a(a(x1)) = x1 + [2] >= [0 0]x1 + [1] = b(c(a(x1))) problem: a(b(x1)) -> a(a(x1)) a(a(x1)) -> b(c(a(x1))) Arctic Interpretation Processor: dimension: 3 interpretation: [0 -& -&] [c](x0) = [0 0 -&]x0 [0 0 -&] , [0 -& 0 ] [a](x0) = [0 0 0 ]x0 [1 1 1 ] , [0 -& -&] [b](x0) = [0 0 -&]x0 [1 1 1 ] orientation: [1 1 1] [1 1 1] a(b(x1)) = [1 1 1]x1 >= [1 1 1]x1 = a(a(x1)) [2 2 2] [2 2 2] [1 1 1] [0 -& 0 ] a(a(x1)) = [1 1 1]x1 >= [0 0 0 ]x1 = b(c(a(x1))) [2 2 2] [1 1 1 ] problem: a(b(x1)) -> a(a(x1)) Arctic Interpretation Processor: dimension: 3 interpretation: [0 -& 0 ] [a](x0) = [0 0 0 ]x0 [1 0 0 ] , [1 -& -&] [b](x0) = [0 0 0 ]x0 [2 1 2 ] orientation: [2 1 2] [1 0 0] a(b(x1)) = [2 1 2]x1 >= [1 0 0]x1 = a(a(x1)) [2 1 2] [1 0 1] problem: Qed